UJI AKTIVITAS KANDUNGAN ANTIOKSIDAN PADA DAUN BANGUN-BANGUN (PLECTRANTHUS AMBOINICUS) SECARA SPEKTROFOTOMETRI ULTRAVIOLET-VISIBLE - Kaban, Vera Estefania; Yusmarlisa, Siti (Fakultas Farmasi Institut Kesehatan Medistra Lubuk Pakam, 2018)
The population explosion that occurred in Indonesia has a profound effect on the quality of life of the community, such as the decline in the level of public health. Therefore leaf plants can be used as medicines that can be useful as antioxidants. Antioxidants are compounds that can inhibit free radicals due to the presence of reactive oxygen, so as to prevent various degenerative diseases. The compounds in the leaves of the buildings include flavonoids, alkaloids and polyphenols. To determine the presence of antioxidant content in wake-up leaves and to determine differences in antioxidant concentrations in wake-up leaves with vitamin C. Samples of leaves of the buildings used were obtained from the Pematang Siantar area, North Sumatra. Sample preparation was carried out by making leaf extracts. The activity test of antioxidant content in the wake-up leaf extract using ultraviolet-visible spectrophotometry. The results showed that there was a decrease in the value of DPPH absorbance given by the wake-up leaf extract test sample with vitamin C. A decrease in the absorbance value indicates a greater DPPH damping activity. The highest DPPH damping activity by leaf extracts of buildings with IC50 values of 20,2842 ppm can be categorized as having very strong DPPH damping activity. There is an antioxidant content with the IC50 category which is very strong in the leaves of the wake-up plant (Plectranthus amboinicus) and the higher the concentration of a test sample of wake-up leaf extract (Plectranthus amboinicus) and BPFI of vitamin C, the absorbance value decreases, The percentage of damping is higher and IC50 is lower, the antioxidant activity is higher.